Feasibility of Smoked Stingrays in Middle Tarakan Village, Tarakan City, North Kalimantan - theresia tere; m gandri haryono; Selly Ratna Sari (Clarias : Jurnal Perikanan Air Tawar, 2023)
Stingrays are bycatch (bycatch) in the catches of fishermen in Tarakan City. This is due to the characteristics of the stingrays and the smell of ammonia which causes not many people to use them, even one of the less desirable fish catches. One of the proper processing of stingrays is by processing them into smoked fish, especially in Tarakan City. The purpose of this study was to analyze the feasibility of smoking fish business in the Middle Tarakan Village, Tarakan City. Data collection was carried out in April-May 2023. Primary data was obtained through observation and interviews with smoked fish entrepreneurs. The results of the study showed that the smoked fish business was carried out in his own smoking house, which was separate from the residential house. The type of fish that is smoked is stingray. The capacity of the smoking tool is 30 kg with the smoking media in the form of coconut shells. The total cost for one production cycle (3 hours) is Rp. 40,000/production; receipt of Rp. 196 million/year and a profit of Rp. 114 million/year. R/C and B/C values ​​were 2.46 and 1.46, PP for 4 days. The results of the smoked fish business are profitable and worth continuing. More and more businesses smoking fish in Tarakan City in the use of fish which are by-catch (by-catch) production is increasing, so as to create new jobs and improve family welfare. PP for 4 days. The results of the smoked fish business are profitable and worth continuing. More and more businesses smoking fish in Tarakan City in the use of fish which are by-catch (by-catch) production is increasing, so as to create new jobs and improve family welfare. PP for 4 days. The results of the smoked fish business are profitable and worth continuing. More and more businesses smoking fish in Tarakan City in the use of fish which are by-catch (by-catch) production is increasing, so as to create new jobs and improve family welfare.